2001
DOI: 10.1515/bc.2001.201
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Inhibits Growth of Human Colon Carcinoma Cells in Vitro by Induction of Apoptosis

Abstract: Epidemiological studies suggest that beta-carotene is able to modulate the risk of cancer. A number of in vitro studies reported that beta-carotene inhibits the growth of cancer cells; however, so far little is known about the molecular mechanisms of the antiproliferative effect of beta-carotene. Here we have investigated the effects of two beta-carotene preparations, (i) beta-carotene dissolved in tetrahydrofuran (final concentration in cell culture medium: 0.5%) and (ii) beta-carotene incorporated in a water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 13 publications
0
28
3
2
Order By: Relevance
“…For instance, human colon carcinoma cells were cultured in the media containing bcarotene (30 lM). After 3 days, intracellular levels of bcarotene and retinol were 22 pmol/10 6 cells and 45 pmol/ 10 6 cells, respectively (Briviba et al 2001). Even though cellular uptake of b-carotene may be dependent on cell types and culture time, we could presume that b-carotene (100 lM) treatment to the medium may increase intracellular levels of b-carotene (about 70 pmol/10 6 cells) and retinol (about 150 pmol/10 6 cells), based on the previous study (Briviba et al 2001).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, human colon carcinoma cells were cultured in the media containing bcarotene (30 lM). After 3 days, intracellular levels of bcarotene and retinol were 22 pmol/10 6 cells and 45 pmol/ 10 6 cells, respectively (Briviba et al 2001). Even though cellular uptake of b-carotene may be dependent on cell types and culture time, we could presume that b-carotene (100 lM) treatment to the medium may increase intracellular levels of b-carotene (about 70 pmol/10 6 cells) and retinol (about 150 pmol/10 6 cells), based on the previous study (Briviba et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…After 3 days, intracellular levels of bcarotene and retinol were 22 pmol/10 6 cells and 45 pmol/ 10 6 cells, respectively (Briviba et al 2001). Even though cellular uptake of b-carotene may be dependent on cell types and culture time, we could presume that b-carotene (100 lM) treatment to the medium may increase intracellular levels of b-carotene (about 70 pmol/10 6 cells) and retinol (about 150 pmol/10 6 cells), based on the previous study (Briviba et al 2001). Further study should be performed to determine the intracellular levels of b-carotene and retinol after treatment of b-carotene in various types of cells and different culture conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Epidemiological studies have indicated that food products which contain lycopene, the most potent antioxidant compound among carotenoids, have chemopreventive effects against cancers and other diseases [2]. Human cell studies showed that lycopene can reduce oxidative DNA damage, stimulate the immune system and facilitate intercellular communication [3]. Many reports on the health benefits of lycopene are attributed to its ability to protect cells against oxidative damage [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Human cell studies showed that lycopene can reduce oxidative DNA damage, stimulate the immune system and facilitate intercellular communication [3]. Many reports on the health benefits of lycopene are attributed to its ability to protect cells against oxidative damage [2][3][4][5][6]. Besides, it has also been observed that silymarin possesses antioxidant, antiinflammatory, antifibrotic and antiproliferative properties.…”
Section: Introductionmentioning
confidence: 99%